Pengaruh Penggunaan Multimedia Animaker dalam Meningkatkan Minat Baca Siswa SDN Malangga Selatan: Penelitian - Selpia; Hasia Marto; Hamna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Low reading interest among fourth grade students in Indonesian language lessons at SDN Malangga Selatan is a common problem. Therefore, this study aims to examine the effectiveness of using Animaker multimedia to increase reading interest. The study used a quantitative pre-experiment method with a one-group pretest-posttest design on 20 students selected through purposive sampling. Data were collected through observation and testing and analyzed using a paired-sample t-test. The analysis revealed a statistically significant increase in reading interest (p < 0.05), evident in the increase of the students' average score from 66 to 80. This study concludes that Animaker multimedia is an effective learning tool for fostering students' interest in reading and is therefore recommended as a more engaging and motivational learning solution.